Paranotocoris Ahmad & Shadab, 1973, a new synonym of Phyllomorpha Laporte, 1833 (Hemiptera: Heteroptera: Coreidae) - Kment, Petr; Rédei, Dávid (Zootaxa, 2013)
The tribe Phyllomorphini Mulsant & Rey, 1870 of the family Coreidae, subfamily Coreinae, is represented in the Palaearctic Region by three genera (Pephricus Amyot & Serville, 1843, Phyllomorpha Laporte, 1833, and Tongorma Kirkaldy, 1900) and four species. Two of them, Pephricus subtilis Montandon, 1913 and Tongorma latreillii (Guérin-Méneville, 1839) are known only from Yemen and represent Afrotropical faunal elements in the Arabian Peninsula. The only truly Palaearctic genus is therefore Phyllomorpha, comprising two species—P. lacerata Herrich-Schäffer, 1835 and P. laciniata (Villers, 1789)—distributed in southern Europe, North Africa, and western Asia from Turkey to Oman, Central Asia, Afghanistan, and Pakistan (Dolling 2006). Ahmad & Shadab (1974) described another monotypic genus from the Pakistani province of Baluchistan, Pronotocoris Ahmad & Shadab, 1974 (type species Paranotocoris echinus Ahmad & Shadab, 1974). Recent study of the original descriptions of both of the taxa drove us to the conclusion that Pronotocoris is a junior subjective synonym of Phyllomorpha, and Pronotocoris echinus a junior subjective synonym of Phyllomorpha lacerata.